Aboriginal young people's perspectives and experiences of accessing sexual health services and sex education in Australia: A qualitative study. Issue 1 (2nd January 2023) - Graham, Simon; Martin, Kacey; Gardner, Kristy; Beadman, Mitchell; Doyle, Michael F.; Bolt, Reuben; Murphy, Dean; Newman, Christy E.; Bell, Stephen; Treloar, Carla; Browne, Annette J.; Aggleton, Peter; et al.
ABSTRACT: Aboriginal and Torres Strait Islander (Aboriginal) young people seek information and access health services for their sexual health needs. This study examined Aboriginal young people's perspectives on sexual health services and sex education in Australia. Overall, 51 Aboriginal people aged 16–26 years were interviewed by peer researchers in Sydney, Australia in 2019–2020. The findings suggest that the internet was used to assess information quickly and confidentially, but Aboriginal young people questioned its reliability and accuracy. Family, Elders and peers were seen as sources of advice because they had real-life experience and highlighted intergenerational learning that occurs in Aboriginal communities. School-based sex education programmes had mixed reviews, with a preference for programmes delivered by external specialists providing anonymity, clear and accurate information about sex and relationships and positive approaches to sex education, including how to gain consent before sex. There was a need identified for school-based programmes to better consider the needs of Aboriginal young people, including those who identified as LGBTQI + . Aboriginal Medical Services were highly valued for providing culturally safe access to services, while sexual health clinics were valued for providing specialised confidential clinical services with low levels of judgement.